Influence of eye movement on lens dose and optic nerve target coverage during craniospinal irradiation. (November 2021) - Hoeben, Bianca A.W.; Seravalli, Enrica; Wood, Amber M.L.; Bosman, Mirjam; Matysiak, Witold P.; Maduro, John H.; van Lier, Astrid L.H.M.W.; Maspero, Matteo; Bol, Gijsbert H.; Janssens, Geert O.
Highlights: While optic nerves are part of the CSI target volume, lenses need to be spared. Lens and optic disc movement for different gaze directions was evaluated in MRI scans. Eye movement influence on lens and optic nerve CSI dose distribution was analyzed. With modern radiotherapy techniques, any eye movement increases the mean lens dose. Maximum eye movements decrease mean orbital optic nerve D98 <10% of prescribed dose. Abstract: Purpose: Optic nerves are part of the craniospinal irradiation (CSI) target volume. Modern radiotherapy techniques achieve highly conformal target doses while avoiding organs-at-risk such as the lens. The magnitude of eye movement and its influence on CSI target- and avoidance volumes are unclear. We aimed to evaluate the movement-range of lenses and optic nerves and its influence on dose distribution of several planning techniques. Methods: Ten volunteers underwent MRI scans in various gaze directions (neutral, left, right, cranial, caudal). Lenses, orbital optic nerves, optic discs and CSI target volumes were delineated. 36-Gy cranial irradiation plans were constructed on synthetic CT images in neutral gaze, with Volumetric Modulated Arc Therapy, pencil-beam scanning proton therapy, and 3D-conventional photons. Movement-amplitudes of lenses and optic discs were analyzed, and influence of gaze direction on lens and orbital optic nerve dose distribution. Results: Mean eye structures' shift from neutral position was greatest in caudal gaze; −5.8±1.2 mm (±SD) for lenses and 7.0±2.0 mm for optic discs. In 3D-conventional plans, caudal gaze decreased Mean Lens Dose (MLD). In VMAT and proton plans, eye movements mainly increased MLD and diminished D98 orbital optic nerve (D98OON ) coverage; mean MLD increased up to 5.5 Gy [total ΔMLD range −8.1 to 10.0 Gy], and mean D98OON decreased up to 3.3 Gy [total ΔD98OON range −13.6 to 1.2 Gy]. VMAT plans optimized for optic disc Internal Target Volume and lens Planning organ-at-Risk Volume resulted in higher MLD over gaze directions. D98OON became ≥95% of prescribed dose over 95/100 evaluated gaze directions, while all-gaze bilateral D98OON significantly changed in 1 of 10 volunteers. Conclusion: With modern CSI techniques, eye movements result in higher lens doses and a mean detriment for orbital optic nerve dose coverage of <10% of prescribed dose.